Long-term clinical and safety outcomes from a single-site phase 1 study of neural stem cell transplantation for chronic thoracic spinal cord injury - Martin, Joel R.; Cleary, Daniel; Abraham, Mickey E.; Mendoza, Michelle; Cabrera, Betty; Jamieson, Catriona; Marsala, Martin; Ciacci, Joseph D. (Cell reports. Medicine, 2024)
We report the long-term results for a phase 1 study of neural stem cell transplantation for chronic spinal cord injury. The trial was registered on ClinicalTrials.gov as NCT01772810. The primary outcome of the trial was to test the feasibility and safety of human spinal cord-derived neural stem cell (NSI-566) transplantation for the treatment of chronic spinal cord injury in four subjects with thoracic two to thoracic twelve spinal cord injury. Here, we report that all four subjects tolerated the stem cell implantation procedure well, and two subjects had durable electromyography-quantifiable evidence of neurological improvement as well as increased neurological motor and sensory scores at five years post-transplantation. [Display omitted] •NSI-566 transplanted in the spinal injury site of patients can be performed safely•NSI-566 transplantation was shown to decrease post-operative pain•NSI-566 transplantation was shown to improve motor and sensory function•NSI-566 transplantation resulted in electrophysiological defined improvement Pre-clinical studies of spinal cord-derived neural stem cell (NSI-566) for spinal cord injury showed promising results. Martin et al. report the results of the 60-month study of a phase 1 first-in-human clinical trial of perilesional NSI-566 implantation in four patients with chronic ASIA-A thoracic spinal cord injury.